2011
DOI: 10.1007/s00107-011-0569-4
|View full text |Cite
|
Sign up to set email alerts
|

Modification of beech veneers with N-methylol-melamine compounds for the production of plywood

Abstract: Rotary cut beech (Fagus sylvatica L.) veneers were treated with two formulations based on N -methylolmelamine (NMM): (1) NMM solution (NMM-1, 10% solid content), (2) fatty acid modified NMM dispersions containing paraffin (with an aluminium salt as catalyst, mNMM-2, 5% solid content). Five treated veneers were bonded with phenol formaldehyde (PF) adhesive to produce plywood in two different processes.The plywood treated with NMM-1 displayed increased shear strength in comparison to the controls, whereas the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…After modification with glyoxal, the WU was significantly reduced and decreased with increasing curing temperature. This phenomenon may be explained by the higher condensation degree of glyoxal; thus, much network was formed, and in addition, at higher curing temperature, more cross-linking may be formed, leading to lower WU (Trinh et al 2012). When the temperature was higher than 120°C, the changing trend was not obvious, which was similar to the ASE shown in Fig.…”
Section: Glyoxal Concentrationsupporting
confidence: 75%
See 1 more Smart Citation
“…After modification with glyoxal, the WU was significantly reduced and decreased with increasing curing temperature. This phenomenon may be explained by the higher condensation degree of glyoxal; thus, much network was formed, and in addition, at higher curing temperature, more cross-linking may be formed, leading to lower WU (Trinh et al 2012). When the temperature was higher than 120°C, the changing trend was not obvious, which was similar to the ASE shown in Fig.…”
Section: Glyoxal Concentrationsupporting
confidence: 75%
“…Clearly, glyoxal modification significantly affected the surface of the modified wood and greatly improved the hydrophobic ability on the wood surface. The increased contact angle may be attributed to the less hydrophilic hydroxyl and less porous wood surface because of the cross-linking reaction and filling effect of the curing hydrophobic glyoxal (Trinh et al 2012). With the addition of the glycol, the contact angle further increased, indicating that the addition of glycol improved the hydrophobic ability of the modified wood.…”
Section: Contact Angle Measurementmentioning
confidence: 86%
“…4b, 5b, 6b, 7b), since all variants show equal weight loss, attributed to accessory material of wood. differences between parallel and perpendicular test direction, an observation that has already been reported in several studies [29,34]. For compressive strength, only marginal differences could be observed between reference 0 , reference and plasma samples independent of grain direction of the outer layers (whereas ''reference 0 '' shows the highest value in perpendicular direction and ''plasma'' in parallel direction, respectively).…”
Section: Dimensional Stability and Mechanical Propertiessupporting
confidence: 68%
“…Trinh et al tested the bending strength of five-layer plywood samples made from vacuum-impregnated beech veneers with melamine resin (solution solid content 5-10%) and bonded with phenol formaldehyde (PF) resin [34]. Dieste et al presented similar results of plywood samples made from DMDHEU vacuum-impregnated beech veneers [39].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In commercial processes for the production of resin-treated plywood, veneers are pre-dried after impregnation. Afterwards, they are either cured at higher temperatures in the veneer dryer (Stamm and Seborg 1942) or in a combined step in the hot press simultaneously with curing the glue (Wepner 2006;Dieste et al 2009;Trinh et al 2012). Varying a number of manufacturing variables, Millett et al (1943) found that drastic drying ([ca.…”
Section: Introductionmentioning
confidence: 99%